Formation of Media Literacy in Teaching Natural Sciences in Primary Grades - G’aniyeva Gulhayo Islom qizi (International Journal on Integrated Education, 2023)
Today, there is a growing need to implement large-scale reforms in the field of improving the teaching of natural sciences on the basis of multimedia tools, international assessment programs and improving the natural and scientific literacy of students in the classroom. In the UN agreement on education, science and culture "Import of materials of educational, spiritual and cultural content", creating broad conditions for the quality of education of learners worldwide, education It is of particular importance to carry out scientific and research work on the introduction of modern innovative technologies into the glue process. In this regard, achieving efficiency and increasing the role and influence of multimedia tools, conceptual study and analysis of existing problems determine the relevance of the topic.